PERAN PSIKOLOGI DALAM KEILMUAN DAN PROFESI - Hidayah, Rifa (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2004)
Psychology as knowledge behavior and psyche or soul, in history, has appeared since Yunani period. At that time, their philosophers try to explain what the soul is and how it works. By the time, the growth of psychology appeared many sects of psychology, such as John Watson, who is to pioneer in behaviorism, John Locke as pioneer of empiricism, Descartes as pioneer of consciousness, etc. Furthermore, psychology, which is usually considered as knowledge about psyche, in fact, it also has to do with other aspects, such as; profession, sport, technical, design, singing, and preventive action in people healthy. Considering how much the important role, which can be handled, psychology scholar should have well and appropriate provisions. That provisions, at least involve three points; 1) expert and professional in knowledge of psychology; methodology and theories, 2) good intelligent, know how to apply and to increase his knowledge, 3) good personality and behavior.Keyword: psychology, knowledge, and profession.